Medicinal plants used during pregnancy, childbirth and postpartum care in India: a systematic review - Sharma, Pramod P.; Sharma, Sakshi P. (International Journal of Research in Medical Sciences, 2023)
Use of plant medicine during pregnancy, childbirth and in postpartum care has grown significantly worldwide and is remarkably well-known in different regions of India. Traditional plant medicine has the potential for treating various diseases/ailments and is evidenced by well-known pharmacopeia of India - Ayurveda. This paper reviews the research papers on plant medicine utilization during pregnancy, childbirth and for postpartum care based on information published from India. Total 206 uses of 146 medicinal plants belong to 69 families, of which 125 are herbs, 39 trees, 26 shrubs and 16 climbers. Plant parts used as medicine for treating various disorders during pregnancy, childbirth and postpartum are 75 leaves, 48 roots, 23 seeds, 19 whole plants, 15 fruits, 11 barks, stem and flower 5 each, gum 2, latex 1, while in 24 cases part used is not specified. The use of plants for treating various disorder/ailments during pregnancy, of these most prevalent use is as a tonic (23 uses) which followed by vomiting (10), abdominal pain (9), to facilitate delivery (6) and so on. Use of plants during childbirth, maximum number of plants used to facilitate deliver (32 uses), for labor pain (15), and to induce labor (12). While use of plants for postpartum care, includes (37 uses) for lactation, (10) for haemorrhage, and 7 for abdominal pain.